Severe Hematochezia Beyond Diverticulosis: Unmasking Superimposed Amoebiasis as the Hidden Trigger Behind Life-Threatening Lower Intestine Bleeding - Linia Nitrika; Herry Purbayu (Current Internal Medicine Research and Practice Surabaya Journal, 2026)
Hematochezia in diverticulosis is due to vascular rupture at the base of the diverticulum. Concomitant amoebiasis causes colonic mucosal ulceration leading to colitis and severe bleeding and may develop into a perforated colon. This combination is rarely reported and poses a diagnostic challenge due to overlapping symptoms. Hematochezia in a patient with diverticulosis caused by “hidden” amoebiasis was reported. It is important to be alert to amoebiasis among patients with diverticulosis and lower intestine bleeding. An 83-year-old man with a history of diverticulosis 10 years ago complains of fresh, bloody diarrhea of 400 cc each time. Concomitant complaints; sweating and weakness.  Examination; anemic conjunctiva, epigastric tenderness, increased bowel sounds, and cold acral. Blood tests; severe anemia (hemoglobin, 6 g/dL), CRP and PCT levels were 9.44 mg/L and 4.37 ng/mL, respectively, suggesting a high risk of sepsis. Endoscopy; Diverticula along the sigmoid to transverse colon, sigmoid erosion. Contrast abdominal CT; diverticulosis along the colon. Feces examination; mucus, erythrocytes, amoeba, and leukocytes. The results indicate diverticulosis and amoebiasis. Blood culture showed gram-negative Pseudomonas. The patient was treated with intravenous fluids, anti-amoeba therapy, and blood transfusions. His condition improved, and he was discharged after 16 days with normal bowel movements, resolved tenderness, a hemoglobin level of 10.2 g/dL, and normal macroscopic and microscopic findings of feces. This case illustrates that amoebiasis can be a hidden and serious cause of hematochezia in patients with diverticulosis. Early recognition and comprehensive management, including hemoglobin monitoring, antiamoebic treatment, and transfusion, are critical for improved outcomes.